Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Cangkang Telur Itik Melalui Proses Sol-Gel Dengan Variasi Rasio Reaktan Ca/P Dan Waktu Aging - Luckita, Gema Kesa; Azis, Yelmida; Akbar, Fajril (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Precipitated Calcium Carbonate (PCC) is a product of nature material that contain calcium carbonate, like duck eggshell. PCC producted by precipitation process with high purity. Hydroxyapatite (HAp) is a crystalline molecule composed of phosphorus and calcium with molecular formula is Ca10(PO4)6(OH)2. Hydroxyapatite is a bioceramic which is widely used as bone graft or teeth, catalyst, and adsorbent. This research aims to study the effect of reactant ratio of Ca/P and aging time on synthesized HAp and to find the best condition of reactant ratio of Ca/P and aging time of hydroxyapatite synthesis in this method. In this research, hydroxyapatite was done by sol-gel method through from PCC formation path from duck egg shell which has 99.6% content. The variations given in this research are the reactant ratio of Ca/P (1.67 and 1.77) and aging time ( 16, 20, 24, 28, and 32 hours). The synthesized hydroxyapatite was analyzed by Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), Scanning Electron Microscopy – Energy Dispersive X-Ray (SEM-EDX). The result showed that the reactant ratio of Ca/P and aging time has effects on the synthesized hydroxyapatite characteristics. The result of FTIR analysis shows that in each sample there are groups of PO43-, OH-, and CO3- which indicate that apatite compound has been formed. The XRD analysis results show that the synthesized hydroxyapatite has X-Ray pattern and the highest intensity peak at angle of 2θ which is very similar to the standard hydroxyapatite from ICDD data (International Centre of Diffraction Data). The optimum condition of reactant ratio of Ca/P and aging time was obtained at the reactant ratio of Ca/P 1.67 and aging time during 32 hours due to the X-Ray pattern and the highest intensity peak at angle of 2θ very similar to the standard hydroxyapatite and having the smallest diameter than other conditions which is 26.8909 nm. The result of SEM-EDX analysis show the hydroxyapatite morphology in the form of agglomerate with molar ratio of Ca/P 1.57 .Keywords : aging, hydroxyapatite, sol-gel method, PCC, synthesis.